2022
DOI: 10.1039/d1mh01889b
|View full text |Cite
|
Sign up to set email alerts
|

Propylene and butylene glycol: new alternatives to ethylene glycol in conjugated polymers for bioelectronic applications

Abstract: Propylene and butylene glycol oligoether chains have been employed as alternatives to ethylene glycol in thiophene based semiconductors for OECTs. Their impact on electrochemical, microstructure, and swelling properties are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
(82 reference statements)
1
31
0
Order By: Relevance
“…Over the past few years, polar and hydrophilic oligo ethylene glycol (OEG) side chains modified conjugated polymers as the channel layers have been developed rapidly, [ 14–17 ] particularly for p‐type (hole transport) OECT devices with the μC* figure of merit up to ≈563 F V −1 cm −1 s −1 given by pgBTTT . [ 18–21 ] Whereas n‐type OECTs are yet much more immature than their p‐type counterparts owing to the lacking of rational n‐type design principles, although several types of n‐type polymeric structures have shown a figure of merit μC* more than 1 F V −1 cm −1 s −1 , [ 22–24 ] most of which presented unsatisfactory performance. [ 25,26 ] This unbalanced situation greatly precludes the development of the lower power consumption complementary circuits and hinders the diversity of bioelectronics applications where n‐type mixed conductors are demanded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, polar and hydrophilic oligo ethylene glycol (OEG) side chains modified conjugated polymers as the channel layers have been developed rapidly, [ 14–17 ] particularly for p‐type (hole transport) OECT devices with the μC* figure of merit up to ≈563 F V −1 cm −1 s −1 given by pgBTTT . [ 18–21 ] Whereas n‐type OECTs are yet much more immature than their p‐type counterparts owing to the lacking of rational n‐type design principles, although several types of n‐type polymeric structures have shown a figure of merit μC* more than 1 F V −1 cm −1 s −1 , [ 22–24 ] most of which presented unsatisfactory performance. [ 25,26 ] This unbalanced situation greatly precludes the development of the lower power consumption complementary circuits and hinders the diversity of bioelectronics applications where n‐type mixed conductors are demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, polar and hydrophilic oligo ethylene glycol (OEG) side chains modified conjugated polymers as the channel layers have been developed rapidly, [14][15][16][17] particularly for p-type (hole transport) OECT devices with the μC* figure of merit up to ≈563 F V −1 cm −1 s −1 given by pgBTTT. [18][19][20][21] Whereas n-type OECTs are yet much more immature than…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Aqueous-based electrolyte has been reported as a promising alternative to organic electrolytes owing to its beneficial properties, such as incombustibility, high ionic conductivity, and low manufacturing cost coming from air insensitivity. [12,13] Therefore, aqueous media has great potential to develop nontoxic, environment-friendly electrochemical devices, such as biosensors, [14] organic electrochemical transistors (OECTs), [15] energy-storage devices, [16] electrochromic devices (ECDs) [17] and organic electronic ion pumps (OEIPs). [18] However, most common D-A copolymers are hydrophobic which originate from alkyl side chains and building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Other studies with spacers ranging from C 3 to C 6 groups in n-type and thiophene homopolymers have shown that excessive swelling can be reduced to improve electronic charge transport. [22,23] The alkyl-group spacers have also shown promise in thermoelectric applications, where the Seebeck coefficient is increased without diminishing energetic order. [24] Another strategy is tuning the conjugated backbone structure of polymers from homopolymers such as poly(3-hexylthiophene) (P3HT) to donor-acceptor (D-A) type copolymers.…”
Section: Introductionmentioning
confidence: 99%